Assessing the impact of substitution rule changes in European football leagues - Zhang, H.; Mathes, J.; Garnica Caparrós, M.; Memmert, D. (International Journal of Sports Science & Coaching, 2025)
Four years after the COVID-19 pandemic, a major change in professional European football was increasing allowed substitutions from three to five players per game. This study explores the effects of this regulatory change on four major European leagues (Ligue 1, La Liga, Serie A, and the Premier League) from the 2015-2016 to the 2022-2023 seasons. Descriptive statistics and a Linear Mixed Model were used to study the impact of the rule change on temporal distribution and number of players substituted. To investigate the change in the immediate impact of substitutions, we created a quantifiable variable and compared pre- and post-rule change results. Additionally, a Difference-in-Difference model examined the new rule's effect on final match outcomes. The results show that clubs are tactically adjusting, with an increased use of halftime substitutions and more flexible second half strategies. Additionally, the variability in the immediate impact of substitution on the scoreline and the decrease in final score difference emphasize the crucial role of substitution in tactics. This study provides a comprehensive understanding of how rule adjustments in football can influence game dynamics and team strategies, offering valuable insights into the tactical adaptations prompted by regulatory changes.